(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Spices are mainly used as additives to diets in different countries, including our country, so it is necessary to ensure that they are free of radioactive substances harmful to human health. This research aimed to measure the concentrations of alpha emitters, and measure the annual effective dose AED resulting from the intake of radon. The CR-39 detector used to measure radon, radium, and uranium concentrations in the 24 spices samples selected from markets. In this work the radon concentrations in the samples were found to vary from 65.102 to 195.30 Bq/m3 with 126.47 Bq/m3 a mean value, this mean value is a small amount over 100 Bq/m3 the reference level limits of the World Health Organization (WHO), below 200 Bq/m3 of the UK Board of National Radiation Protection (NRPB) limits and below the level of the European Recommendation Commission. The annual radon effective dose varied between 1.642-4.927 mSv/y which is within the range of 0.2-10 mSv/y of (UNSCEAR). Radium contents vary between 0.446-1.367 Bq/Kg with 0.943 Bq/Kg as a mean value. The range of uranium activity concentrations is between 4.408-13.520 Bq/Kg with a mean value of 9.322 Bq/Kg. This work identified and measured the specified concentrations of radionuclide present in spices showed that spices are safe for consumption.